2021
DOI: 10.1186/s13047-021-00501-8
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of diabetes‐related foot disease among older adults in New South Wales, Australia: evidence from a population‐based study

Abstract: Background Diabetes-related foot is the largest burden to the health sector compared to other diabetes-related complications in Australia, including New South Wales (NSW). Understanding of social determinants of diabetes-related foot disease has not been definitive in Australian studies. This study aimed to investigate the social determinants of diabetes-related foot disease in NSW. Methodology The first wave of the 45 and Up Study survey data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…Our finding is also corroborated by the study by Zhang et al (2020), where they reported that the burden disproportionately affected males and the older aged population globally 7 . Although females in Australia have a higher life expectancy, the higher YLD burden could be due to the higher prevalence of diabetic foot complications among males for most age groups, as documented by several studies 23,31‐34 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding is also corroborated by the study by Zhang et al (2020), where they reported that the burden disproportionately affected males and the older aged population globally 7 . Although females in Australia have a higher life expectancy, the higher YLD burden could be due to the higher prevalence of diabetic foot complications among males for most age groups, as documented by several studies 23,31‐34 …”
Section: Discussionsupporting
confidence: 91%
“…7 Although females in Australia have a higher life expectancy, the higher YLD burden could be due to the higher prevalence of diabetic foot complications among males for most age groups, as documented by several studies. 23,[31][32][33][34] Our study found that the number of deaths due to DFUIG was 7 per 100 000 people in 2011 among individuals aged 45 years and older. At this rate, the total number of deaths due would equate to 587 deaths due to DFUIG in Australia.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A population survey study of 33,663 people, in which demographic data but no comparisons were given, found that as the marriage rate decreased, more serious complications increased (18). This situation can be interpreted as married people being more motivated to care for their chronic illnesses, and their partners can help in their care.…”
Section: Resultsmentioning
confidence: 99%
“…Work status, stability, job kind, and working circumstances have all been considered. Employees of significant corporations have their work situations, qualifications, and salary recorded in occupational tiers of job categories [ 4 ].…”
Section: Reviewmentioning
confidence: 99%